Activation of Prefrontal Cortex in Process of Oral and Finger Shape Discrimination: fNIRS Study - Narita, Noriyuki; Kamiya, Kazunobu; Iwaki, Sunao; Ishii, Tomohiro; Endo, Hiroshi; Shimosaka, Michiharu; Uchida, Takeshi; Kantake, Ikuo; Shibutani, Koh (Frontiers in Neuroscience, 2021)
Background The differences in brain activities of the insular and the visual association cortices has been reported between oral and manual stereognosis. However, these results were not conclusive because of the inherent differences in task performance related motor sequence conditions. We hypothesized that involvement of prefrontal cortex may be different between finger and oral shape discrimination. This study was conducted to clarify temporal changes in prefrontal activities occurring during the processes of oral and finger tactual shape discrimination using prefrontal fNIRS. Methods Six healthy right-handed males [aged 30.8 ± 8.2 years (mean ± SD)] were enrolled. Measurements of prefrontal activities were performed using a 22-channel fNIRS device (ETG-100, Hitachi Medical Co., Chiba, Japan) during experimental blocks that included resting state (REST), nonsense shape discrimination (SHAM), and shape discrimination (SHAPE). Results No significant difference was presented in regard to number of correct answers during trials between oral and finger SHAPE discrimination. Additionally, the statistical difference for prefrontal fNIRS activity between oral and finger shape discrimination was noted in CH 1. Finger SHAPE, as compared with SHAM, presented the temporally shifting of onset and burst in prefrontal activities from FPA to OFC. In contrast, oral SHAPE as compared with SHAM showed the temporally overlapped in onset and burst of prefrontal activities in DLPFC/FPA/OFC. Conclusion The prefrontal activities temporally shifting from FPA to OFC during SHAPE as compared with SHAM may suggest the segregated serial prefrontal processing from manipulation of target image to the decision making during the process of finger shape discrimination. In contrast, the temporally overlapped prefrontal activities of DLPFC/FPA/OFC in oral SHAPE block may suggest the parallel procession of the repetitive involvement of generation, manipulation, and decision making in order to form the reliable representation of target objects.